2012
DOI: 10.1155/2012/632040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Jet Inclination Angle and Hole Exit Shape on Vortical Flow Structures in Low-Reynolds Number Jet in Cross-Flow

Abstract: Numerical studies have been performed to visualize vortical flow structures emerged from jet cross-flow interactions. A single square jet issuing perpendicularly into a cross-flow was simulated first, followed by two additional scenarios, that is, inclined square jet at angles of 30• and 60• and round and elliptic jets at an angle of 90 • , respectively. The simulation considers a jet to cross-flow velocity ratio of 2.5 and a Reynolds number of 225, based on the free-stream flow quantities and the jet exit wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…They concluded that the film-cooling performance is affected by the counter-rotating secondary flow structure downstream of the jet exit in the streamwise injection cases, which can be improved by controlling the strength of the counter-rotating vortex pair. In a recent investigation, Yao et al [33] used the direct numerical simulation (DNS) to predict the flow structures emerged from the interaction of a single square jet issuing into a cross-flow at a velocity ratio of 2.5 and a free stream Reynolds number of 225. Three different kinds of jet geometries have been considered, normal jet, inclined jet at angles of 30 and 60 deg, and round and elliptic jets at an angle of 90 deg.…”
Section: Blowing Ratio Effectsmentioning
confidence: 99%
“…They concluded that the film-cooling performance is affected by the counter-rotating secondary flow structure downstream of the jet exit in the streamwise injection cases, which can be improved by controlling the strength of the counter-rotating vortex pair. In a recent investigation, Yao et al [33] used the direct numerical simulation (DNS) to predict the flow structures emerged from the interaction of a single square jet issuing into a cross-flow at a velocity ratio of 2.5 and a free stream Reynolds number of 225. Three different kinds of jet geometries have been considered, normal jet, inclined jet at angles of 30 and 60 deg, and round and elliptic jets at an angle of 90 deg.…”
Section: Blowing Ratio Effectsmentioning
confidence: 99%
“…The results showed that as the DR increases the penetration of the jet into the cross-flow increases for a constant VR. In a recent investigation, Yao et al [15] simulated a single square jet issuing into a cross-flow at a VR of 2.5 and a freestream Reynolds number of 225 using direct numerical simulation (DNS) approach. Normal jet, inclined jet at angles of 30 • and 60 • , and round and elliptic jets at an angle of 90 • were used.…”
Section: Introductionmentioning
confidence: 99%